KONVALIDASI PERKAWINAN KATOLIK YANG TIDAK SAH - Paulinus Tibo; Missa Sitepu; Benediktus Benteng Kurniadi; Ona Sastri Lumban Tobing (Jurnal Pelayanan Pastoral, 2021)
The purpose of this research is to find out how people understand the validity of marriage and the implementation of marriage validation for the validity of Catholic marriages in the Stasi Saint Paulus Sukanalu, Paroki Santa Perawan Maria Diangkat Ke Surga Kabanjahe. This research employs a qualitative approach. The informants in this research were KDPS, a valid Catholic spouse and illegitimate Catholic married couples. Marriage in the Catholic Church has three elements of validity: agreement, confirmation system and free status. The unfulfilled one of the elements results in the marriage being invalid and not recognized by the Church and to legalize it by accepting validation. The finding of this research is that people understand the elements of the validity of Catholic marriage but have not been able to apply validation to live as a member of the Church. Most of the people, especially the illegitimate spouses, still receive the right to be a Catholic even though they should not be accepted.